3D Bio-Printing Fabrication and Properties of Graphene Dispersion-based Hybrid Scaffolds. (September 2020) - Peng, Jun; Li, Liying; Nie, Yi; Liu, Tianqing; Song, Kedong
Abstract: Peripheral nerve is an important tissue of human body, which is distributed in various parts of human body, and has the function of connecting central nervous system and other organs. The self-repair ability of the nervous system is poor. However, 3D bio-printed neural tissue-engineered scaffolds offer a promising solution. In this study, graphene (Gr) was dispersed by a certain method, and then blended with gelatin (Gel) and sodium alginate (SA) to prepare a mixed bio-ink. Performance of different ratios of bio-ink was evaluated to determine the best printing ratio of the material. Four groups of Gr/Gel/SA scaffolds (The concentrations of graphene were 0%, 0.02%, 0.08% and 0.2% (w/v%), respectively) were prepared by using 3D printing technology. The mechanical strength, contact angle, degradation rate and water absorption of bio-scaffolds were compared to select the most suitable scaffold to support cell proliferation and differentiation, PC12 cells were used to study the biocompatibility of the scaffolds. This article aims to get the most optimized scaffolds.